Use of Chemical and Colorimetric Changes to Age Cryptotermes brevis Frass for Termite Management - William Haigh; Babar Hassan; Tengfei Yi; R. Andrew Hayes (Insects)
Drywood termites are problematic timber pests worldwide. Cryptotermes brevis, the West Indian drywood termite, is among the most important of these pests, in part due to its cryptic nature, making it hard to detect in structures and thereby easy to transport. Primary detections are commonly made by the observation of frass deposits evacuated through kick-holes, often leading to fumigation of the building to effectively eradicate the pest. However, after treatment, new frass piles are often discovered. It is, then, challenging to determine whether this frass represents reinfestation or is simply old frass dislodged from inactive nests. This may lead to unchecked termite proliferation or expensive fumigation when it is not needed. The ability to assess the age of the found frass would allow inspectors to determine whether a new infestation has occurred. Photocolorimetry has indicated that frass darkens over time, but large differences in the starting color of frass samples limit the usefulness of this as an aging method. Gas chromatographic-mass spectrometric analysis of the hexane extracts of C. brevis frass samples aged 0–22 months found differences between fresh frass (under 6 months) and those aged over 12 months but could not distinguish between 6- and 12-month-aged frass. Eight compounds accounted for over 70% of the differences between samples and are, thus, targets for chemical analysis of frass of unknown age. While this chemical frass analysis requires fairly sophisticated analytical tools, the cost associated with these processes would pale in comparison with those for unnecessarily fumigating a structure and thus merits further refinement to increase the accessibility of the method.